Education and training activities in forensic and biomedical sciences: The laser scanner technology - Roberta Somma; Gennaro Baldino; Alessio Altadonna; Alessio Asmundo; Vincenzo Fodale; Patrizia Gualniera; Cristina Mondello; Chiara Pennisi; Marcello Raffaele; Fabio Salmeri; Elvira Ventura Spagnolo; Daniela Sapienza (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2023)

(untitled)
The paper reports the results of training experiences in the field of education in forensic and biomedical sciences carried out during two editions of summer schools. Two simulated serious crimes, involving dummies used as victims, were prepared for practitioners in outdoor places. The scenes simulate a suspect murder case of homicide with staging and a corpse concealment with dismembered human remains found into a clandestine grave, respectively. During the simulations, laser scanning technology was applied to reproduce the outdoor crime scenes in order to verify the capacity of the innovative technique as advantageous tool during educational and forensic training. Judicial inspections conducted during the simulation provided preliminary physical evidence, in the fields of forensic medicine, forensic geology, and engineering, highlighting the importance of the multidisciplinary approach. These experiences, through the use of the laser scanner that allowed for the recreation of virtual environments in which practitioners were able to confront crime scenes, demonstrated how such an approach can be useful in education and training activities.